2015
DOI: 10.1111/medu.12744
|View full text |Cite
|
Sign up to set email alerts
|

Variables that affect the process and outcome of feedback, relevant for medical training: a meta-review

Abstract: The larger picture of variables that influence the process and outcome of feedback, relevant for medical education, shows many open spaces. We suggest that targeted studies be carried out to expand our knowledge of these important aspects of feedback in medical education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 88 publications
(303 reference statements)
7
87
0
6
Order By: Relevance
“…Therefore, the aim of this scoping review was to bring together information in an easily accessible way to support the optimal design, implementation and reporting of workplace-based feedback interventions for early career professionals. This complements previous research, such as that of van der Ridder et al, 13 whose work focuses on undergraduate education and assessments (rather than ECPs in busy workplace environments and naturally occurring workplace-based measures) and whose primary audience is researchers (rather than feedback intervention designers). Given the complexity of feedback interventions and their variable reported impact, our methodological approach sought to identify literature that provided in-depth accounts of feedback strategies that aimed to change the behaviour of ECPs, from research involving a wide range of study designs and from different professions.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, the aim of this scoping review was to bring together information in an easily accessible way to support the optimal design, implementation and reporting of workplace-based feedback interventions for early career professionals. This complements previous research, such as that of van der Ridder et al, 13 whose work focuses on undergraduate education and assessments (rather than ECPs in busy workplace environments and naturally occurring workplace-based measures) and whose primary audience is researchers (rather than feedback intervention designers). Given the complexity of feedback interventions and their variable reported impact, our methodological approach sought to identify literature that provided in-depth accounts of feedback strategies that aimed to change the behaviour of ECPs, from research involving a wide range of study designs and from different professions.…”
Section: Resultssupporting
confidence: 63%
“…Individuals also need feedback that helps them reflect on how closely their performance matches that of the model. Different feedback types can be used but they vary in the degree to which they influence successful behavior (Hogarth et al, 1991; Shute, 2008; van de Ridder et al, 2015). Process feedback, according to Kulhavy (1977), becomes a “form of new instruction, rather than informing the student solely about correctness” (p. 212).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that few published studies have examined feedback receptivity and feedback provision. 24 These aspects are directly addressed by the tool studied as it specifically lists actions to assess for both the milestones and procedural key steps and, in so doing, labels learner behaviors to be performed and assessed.…”
Section: Discussionmentioning
confidence: 99%